помогите выполнить два выделенных задания

  • 1)
    ( X + 3 ) / ( X^2 - 6X - 27) = 1 / ( X - 9 ) 
    ....................................
    X^2 - 6X - 27 = ( X - 9 )*( X + 3 ) 
    D = 36 - 4*1*(-27) = 36 + 108 = 144
    V D = 12
    X1 = ( 6 + 12 ) : 2 = 9 
    X2 = ( 6 - 12 ) : 2 = - 3 
    ......................................
    2)
    (3X^2 + 8X - 3 ) / ( 9X^2 - 1 ) = ( X + 3 ) / ( 9 * ( X + 1/3 )) = ( X + 3) / ( 9X + 3 ) 
    .........................................
    3X^2 + 8X - 3 = ( X - 1/3)*( X + 3 )
    D = 64 - 4*3*(-3) = 64 + 36 = 100
    V D = 10
    X1 = ( - 8 + 10 ) : 6 = 2/6 = 1/3 
    X2 = ( - 18 ) : 6 = ( - 3 )
    .............................................
    9X^2 - 1 = 9 * ( X^2 - 1/9 ) = 9 * ( X - 1/3)*( X + 1/3)
    .................................................




See also: